High-capacity easy-to-activate TiFe hydrogen storage alloy and preparation method thereof
By adding Nb, Cr, Co and rare earth elements to the TiFe hydrogen storage alloy, the lattice structure and composition are optimized, and the problems of poor activation performance and low hydrogen storage capacity of TiFe hydrogen storage alloy are solved, and rapid hydrogen absorption and high cycle stability are achieved at room temperature.
Patent Information
- Application Number
- CN202510131242.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-06
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2045-02-06
AI Technical Summary
The activation performance of TiFe hydrogen storage alloys is poor, and it needs to be activated for a long time under harsh conditions, and the hydrogen storage volume is low, which affects its application prospects.
By adding Nb, Cr, Co and rare earth elements to the TiFe alloy, the CsCl phase, Ti0.97Nb0.03 phase, Ti0.7Nb0.3 phase and rare earth phase are formed, the lattice parameters of the main phase of TiFe are increased, the room temperature activation performance is improved, and the hydrogen absorption and discharge platform is optimized.
It realizes the rapid and direct hydrogen absorption at room temperature, the activation time is short, the total hydrogen storage capacity is greater than 2wt%, the effective hydrogen release capacity is greater than 1.7wt%, and the capacity retention rate of 200 cycles is greater than 95%, which improves the hydrogen storage capacity and activation performance.
Smart Images

Figure CN119614979A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of hydrogen storage alloys, and in particular to a high-capacity and easily activated TiFe hydrogen storage alloy and a preparation method thereof. Background Art
[0002] Hydrogen energy is a clean form of energy with high energy density and complete decarbonization. It is an ideal substitute for fossil fuels. Efficient and safe hydrogen storage is a key problem in the development of hydrogen energy. Among the existing hydrogen storage methods, high-pressure gaseous hydrogen storage is currently a more common hydrogen storage method. The main problems are large volume and poor safety. Converting gaseous hydrogen into liquid hydrogen for storage in a low-temperature environment can obtain a high volume energy density. However, maintaining the low temperature requires a large amount of energy, which accounts for about 30% of its stored energy.
[0003] Storing hydrogen in the form of metal hydrides is a feasible idea, which has the advantages of large volume hydrogen storage density, good safety and high energy efficiency. At present, various systems have been developed, including AB5 type, AB type, AB2 type, superlattice type, V-based solid solution and magnesium-based. Among them, AB5 type hydrogen storage alloy has been applied, but the hydrogen storage capacity is relatively low (about 1.5wt%); although the V-based solid solution has a high hydrogen storage capacity (about 3.5wt%), the cost of V is high; the dehydrogenation temperature of magnesium-based hydrogen storage alloy is above 250 ℃, which is difficult to use directly; the hydrogen storage capacity of AB type, AB2 type and superlattice type is close (about 1.9wt%), and AB type alloy has obvious cost advantages.
[0004] AB type hydrogen storage alloys are mainly represented by TiFe alloys. TiFe alloys are mainly CsCl phases. After absorbing hydrogen, they form two hydrides, TiFeH and TiFeH2, which correspond to the two platforms in the PCT curve. The theoretical hydrogen storage capacity reaches 1.86 wt%. TiFe alloys have the advantages of abundant raw material sources and low cost, rich application scenarios, and broad prospects. At present, poor activation performance is a key issue restricting the application of TiFe hydrogen storage alloys. There is an oxide layer on the surface of TiFe alloys, which hinders the entry of hydrogen. It needs to be activated for a long time under harsh conditions (6.5MPa hydrogen pressure, 673 K) to achieve TiFe alloy hydrogen storage. In addition, the phase composition is crucial to the hydrogen storage performance of TiFe. The formation of TiFe phase requires Ti to be in the range of 49.7-52.5at%. Deviation will form TiFe2 phases that are difficult to absorb hydrogen and other phases that cannot reversibly absorb hydrogen, affecting the capacity. Summary of the invention
[0005] The present invention provides a high-capacity and easily activated TiFe hydrogen storage alloy and a preparation method thereof, so as to improve the activation performance of the TiFe hydrogen storage alloy, realize rapid hydrogen absorption at room temperature, reduce activation conditions, increase the lattice parameter of the TiFe main phase, and improve the hydrogen storage capacity.
[0006] In order to solve the above technical problems, one of the purposes of the present invention is to provide a high-capacity and easily activated TiFe hydrogen storage alloy, the composition formula of the hydrogen storage alloy is: Ti a Fe 49-b-c Cr b Co1N c RE d , among which, 50≤a≤55, 2≤b≤4, 1≤c≤5, 1≤d≤4, and RE is a rare earth element.
[0007] By adopting the above scheme, the hydrogen storage alloy of the present application has CsCl phase (TiFe), Ti 0.97 Nb 0.03 Phase (c=1), Ti 0.7 Nb 0.3 phase (c>1) and rare earth phase, the main phase is CsCl phase (TiFe); Nb is used to partially replace Fe in the TiFe alloy. Nb can exist in the TiFe alloy in the form of solid solution, increase the lattice parameter of the TiFe main phase, thereby increasing the hydrogen storage capacity and reducing hysteresis; and Nb can also combine with excess Ti in the TiFe alloy to form a separate phase, preferentially absorb hydrogen, which is beneficial to improving the room temperature activation performance of the TiFe hydrogen storage alloy, and realizing the direct hydrogen absorption of the TiFe alloy at room temperature with a short activation time; the presence of rare earth elements is beneficial to improving the cycle stability and activation performance, Co is beneficial to improving the hydrogen absorption and desorption platform and platform flatness, and Cr is helpful to improve the activation performance of TiFe, so that the total hydrogen storage capacity of the hydrogen storage alloy is greater than 2wt% at 40°C and hydrogen pressure of 9.5MPa, the effective hydrogen desorption capacity is greater than 1.7 wt%, the capacity retention rate after 200 cycles is greater than 95%, and hydrogen can be quickly and directly absorbed at room temperature, reaching the maximum hydrogen storage capacity within 4h.
[0008] As a preferred embodiment, the RE is at least one of La, Ce, Y, Sm and Pr.
[0009] As a preferred embodiment, the hydrogen storage alloy is composed of Ti 52 Fe 45 Cr2Co1Nb2La2、Ti 50 Fe 43 Cr4Co1Nb2Y2、Ti 55 Fe 46 Cr2Co1Nb1Pr3、Ti 52 Fe 42 Cr2Co1Nb5Ce1、Ti 53 Fe 45 Cr3Co1Nb1La1、Ti 50 Fe 45 Any one of Cr2Co1Nb2La4.
[0010] In order to solve the above technical problems, one of the purposes of the present invention is to provide a method for preparing a high-capacity and easily activated TiFe hydrogen storage alloy, comprising the following steps: The ingredients are prepared according to the stoichiometric ratio of the hydrogen storage alloy components, and then the raw materials are melted by arc melting. The melting time is 3-10 minutes each time, and the melting is repeated 5-10 times. The melting temperature does not exceed 3000° C. After cooling, the raw materials are crushed and sieved to obtain a powdered hydrogen storage alloy.
[0011] The present application uses multiple smelting processes, and defects such as grain boundaries and coarse grains may appear in the crystal structure of the alloy during the smelting process. Multiple solidification and remelting help to refine the grains and improve the density and uniformity of the crystal structure. The smelting temperature is controlled not higher than 3000°C, which can avoid the volatilization of Cr, Co and rare earth elements in this temperature environment, resulting in a decrease in the content of Cr, Co and rare earth elements in the alloy and affecting the activation performance and hydrogen storage capacity.
[0012] As a preferred solution, the raw material of the hydrogen storage alloy is a metal element with a purity of more than 99%.
[0013] As a preferred solution, during the smelting process, the smelting current is 120-180A and the inert gas pressure is 400-800Pa.
[0014] As a preferred embodiment, the inert gas is at least one of argon, nitrogen and helium.
[0015] As a preferred solution, the mesh size of the hydrogen storage alloy is 200-400 meshes.
[0016] As a preferred solution, a vibration mill is used to crush the alloy ingot, and the vibration mill time is 10-20 s.
[0017] As a preferred embodiment, the smelting temperature is 2500-3000°C.
[0018] Compared with the prior art, the present invention has the following beneficial effects: 1. In the hydrogen storage alloy of the present application, Nb exists in the TiFe alloy in the form of a solid solution, which increases the lattice parameter of the TiFe main phase, thereby increasing the hydrogen storage capacity and reducing hysteresis; and Nb can also combine with excess Ti in the TiFe alloy to form a separate phase, preferentially absorbing hydrogen, which is beneficial to improving the room temperature activation performance of the TiFe hydrogen storage alloy. The presence of rare earth elements is beneficial to improving the cycle stability and activation performance. Co is beneficial to improving the hydrogen absorption and desorption platform and platform flatness. Cr helps to improve the activation performance of TiFe, enabling the TiFe alloy to directly absorb hydrogen at room temperature with a short activation time.
[0019] 2. The hydrogen storage alloy of the present application has CsCl phase (TiFe), Ti 0.97 Nb0.03 Phase (c=1), Ti 0.7 Nb 0.3 phase (c>1) and rare earth phase, with the main phase being CsCl phase (TiFe). At 40°C and hydrogen pressure of 9.5MPa, the total hydrogen storage capacity is greater than 2wt%, the effective hydrogen release capacity is greater than 1.7 wt%, the capacity retention rate after 200 cycles is greater than 95%, and it can absorb hydrogen quickly and directly at room temperature, reaching the maximum hydrogen storage capacity within 4h. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 : XRD images of a high-capacity and easily activated TiFe hydrogen storage alloy in Examples 1 and 5 of the present invention; Figure 2 : PCT curves of TiFe hydrogen storage alloys prepared in Examples 1 and 4 of the present invention and Comparative Example 4 at different pressures, temperatures and compositions. DETAILED DESCRIPTION
[0021] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0022] The sources and types of raw materials used in the examples and comparative examples of the present application are all commercially available unless otherwise specified, and the same raw materials are used in parallel experiments.
[0023] Example 1 A high-capacity and easily activated TiFe hydrogen storage alloy, the alloy composition is: Ti 52 Fe 45 Cr2Co1Nb2La2, comprising Ti, Fe, Cr, Co, Nb and La in a stoichiometric ratio of 52:45:2:1:2:2, and a preparation method thereof comprising the following steps: According to Ti 52 Fe 45 The stoichiometric ratio of the Cr2Co1Nb2La2 alloy components is used for formulation. The purity of the metal raw materials is greater than 99%, and the total mass of the alloy is 10 g. The raw materials are then melted in a vacuum arc with a melting current of 150A, a melting temperature of 2500-3000°C, an argon pressure of 600Pa, and a melting time of 3min each time. The alloy ingot is turned over and the melting is repeated 5 times. After cooling, the alloy ingot is crushed by a vibration mill for 20 s. After screening, a 300-mesh powder hydrogen storage alloy is obtained.
[0024] Example 2 A high-capacity and easily activated TiFe hydrogen storage alloy, the alloy composition is: Ti 50 Fe 43 Cr4Co1Nb2Y2, comprising Ti, Fe, Cr, Co, Nb and Y in a stoichiometric ratio of 50:43:4:1:2:2, and a preparation method thereof comprising the following steps: According to Ti 50 Fe 43 The stoichiometric ratio of the Cr4Co1Nb2Y2 alloy components is used for mixing. The purity of the metal raw materials is greater than 99%, and the total mass of the alloy is 10 g. The raw materials are then melted in a vacuum arc with a melting current of 160A, a melting temperature of 2500-3000°C, an argon pressure of 600Pa, and a melting time of 3min each time. The alloy ingot is turned over and the melting is repeated 6 times. After cooling, the alloy ingot is crushed by a vibration mill for 20 s. After screening, a 300-mesh powder hydrogen storage alloy is obtained.
[0025] Example 3 A high-capacity and easily activated TiFe hydrogen storage alloy, the alloy composition is: Ti 55 Fe 46 Cr2Co1Nb1Pr3, comprising Ti, Fe, Cr, Co, Nb and Pr in a stoichiometric ratio of 55:46:2:1:1:3, and a preparation method thereof comprising the following steps: According to Ti 55 Fe 46 The stoichiometric ratio of the Cr2Co1Nb1Pr3 alloy components is used for mixing. The purity of the metal raw materials is greater than 99%, and the total mass of the alloy is 10 g. The raw materials are then melted in a vacuum arc with a melting current of 150 A and an argon pressure of 600 Pa. The melting time for each time is 3 min. The alloy ingot is turned over and the melting is repeated 5 times. After cooling, the alloy ingot is crushed by a vibration mill for 20 s. After screening, a 300-mesh powder hydrogen storage alloy is obtained.
[0026] Example 4 A high-capacity and easily activated TiFe hydrogen storage alloy, the alloy composition is: Ti 52 Fe 42 Cr2Co1Nb5Ce1, comprising Ti, Fe, Cr, Co, Nb and Ce in a stoichiometric ratio of 52:42:2:1:5:1, and a preparation method thereof comprising the following steps: According to Ti 52 Fe 42The stoichiometric ratio of the Cr2Co1Nb5Ce1 alloy components is used for mixing. The purity of the metal raw materials is greater than 99%, and the total mass of the alloy is 10 g. The raw materials are then melted in a vacuum arc with a melting current of 150A, a melting temperature of 2500-3000°C, an argon pressure of 600Pa, and a melting time of 3min each time. The alloy ingot is turned over and the melting is repeated 5 times. After cooling, the alloy ingot is crushed by a vibration mill for 20 s. After screening, a 300-mesh powder hydrogen storage alloy is obtained.
[0027] Example 5 A high-capacity and easily activated TiFe hydrogen storage alloy, the alloy composition is: Ti 53 Fe 45 Cr3Co1Nb1La1, comprising Ti, Fe, Cr, Co, Nb and La in a stoichiometric ratio of 53:45:3:1:1:1, and a preparation method thereof comprising the following steps: According to Ti 53 Fe 45 The stoichiometric ratio of the Cr3Co1Nb1La1 alloy components is used for mixing. The purity of the metal raw materials is greater than 99%, and the total mass of the alloy is 10 g. The raw materials are then melted in a vacuum arc with a melting current of 150A, a melting temperature of 2500-3000°C, an argon pressure of 600Pa, and a melting time of 3min each time. The alloy ingot is turned over and the melting is repeated 5 times. After cooling, the alloy ingot is crushed by a vibration mill for 20 s. After screening, a 300-mesh powder hydrogen storage alloy is obtained.
[0028] Example 6 A high-capacity and easily activated TiFe hydrogen storage alloy, the alloy composition is: Ti 50 Fe 45 Cr2Co1Nb2La4, comprising Ti, Fe, Cr, Co, Nb and La in a stoichiometric ratio of 50:45:2:1:2:4, and a preparation method thereof comprising the following steps: According to Ti 50 Fe 45 The stoichiometric ratio of the Cr2Co1Nb2La4 alloy components is used for formulation. The purity of the metal raw materials is greater than 99%, and the total mass of the alloy is 10 g. The raw materials are then melted in a vacuum arc with a melting current of 150A, a melting temperature of 2500-3000°C, an argon pressure of 600Pa, and a melting time of 3min each time. The alloy ingot is turned over and the melting is repeated 5 times. After cooling, the alloy ingot is crushed by a vibration mill for 20 s. After screening, a 300-mesh powder hydrogen storage alloy is obtained.
[0029] Comparative Example 1 A TiFe hydrogen storage alloy, the composition of the alloy is: Ti 52 Fe 48 Cr6Co1Nb2La2, comprising Ti, Fe, Cr, Co, Nb and La in a stoichiometric ratio of 52:48:6:1:2:2, and a preparation method thereof comprising the following steps: According to Ti 52 Fe 48 The stoichiometric ratio of the Cr6Co1Nb2La2 alloy components is used for mixing. The purity of the metal raw materials is greater than 99%, and the total mass of the alloy is 10 g. The raw materials are then melted in a vacuum arc with a melting current of 150A, a melting temperature of 2500-3000°C, an argon pressure of 600Pa, and a melting time of 3min each time. The alloy ingot is turned over and the melting is repeated 5 times. After cooling, the alloy ingot is crushed by a vibration mill for 20 s. After screening, a 300-mesh powder hydrogen storage alloy is obtained.
[0030] Comparative Example 2 A TiFe hydrogen storage alloy, the composition of the alloy is: Ti 55 Fe 40 Cr2Co1Nb7La2, comprising Ti, Fe, Cr, Co, Nb and La in a stoichiometric ratio of 55:40:2:1:7:2, and a preparation method thereof comprising the following steps: According to Ti 55 Fe 40 The stoichiometric ratio of the Cr2Co1Nb7La2 alloy components is used for mixing. The purity of the metal raw materials is greater than 99%, and the total mass of the alloy is 10 g. The raw materials are then melted in a vacuum arc with a melting current of 150A, a melting temperature of 2500-3000°C, an argon pressure of 600Pa, and a melting time of 3min each time. The alloy ingot is turned over and the melting is repeated 5 times. After cooling, the alloy ingot is crushed by a vibration mill for 20 s. After screening, a 300-mesh powder hydrogen storage alloy is obtained.
[0031] Comparative Example 3 A TiFe hydrogen storage alloy, the alloy composition is: Ti 52 Fe 43 Cr2Co3Nb2La2, comprising Ti, Fe, Cr, Co, Nb and La in a stoichiometric ratio of 52:43:2:3:2:2, and a preparation method thereof comprising the following steps: According to Ti 52 Fe 43The stoichiometric ratio of the Cr2Co3Nb2La2 alloy components is used for formulation. The purity of the metal raw materials is greater than 99%, and the total mass of the alloy is 10 g. The raw materials are then melted in a vacuum arc with a melting current of 150A, a melting temperature of 2500-3000°C, an argon pressure of 600Pa, and a melting time of 3min each time. The alloy ingot is turned over and the melting is repeated 5 times. After cooling, the alloy ingot is crushed by a vibration mill for 20 s. After screening, a 300-mesh powder hydrogen storage alloy is obtained.
[0032] Comparative Example 4 A TiFe hydrogen storage alloy, the alloy composition is: Ti 55 Fe 48 La2, comprising Ti, Fe and La in a stoichiometric ratio of 55:48:2, and a preparation method thereof comprising the following steps: According to Ti 55 Fe 48 The La2 alloy components are prepared according to the stoichiometric ratio. The purity of the metal raw materials is greater than 99%, and the total mass of the alloy is 10 g. The raw materials are then melted in a vacuum arc with a melting current of 150A, a melting temperature of 2500-3000°C, an argon pressure of 600Pa, and each melting time of 3min. The alloy ingot is turned over and the melting is repeated 5 times. After cooling, the alloy ingot is crushed by a vibration mill for 20 s. After screening, a 300-mesh powder hydrogen storage alloy is obtained.
[0033] Comparative Example 5 A TiFe hydrogen storage alloy, the alloy composition is: Ti 52 Fe 48 Cr2Co1Nb2, comprising Ti, Fe, Cr, Co and Nb in a stoichiometric ratio of 52:48:2:1:2, and a preparation method thereof comprising the following steps: According to Ti 52 Fe 48 The stoichiometric ratio of the Cr2Co1Nb2 alloy components is used for mixing. The purity of the metal raw materials is greater than 99%, and the total mass of the alloy is 10 g. The raw materials are then melted in a vacuum arc with a melting current of 150A, a melting temperature of 2500-3000°C, an argon pressure of 600Pa, and each melting time of 3min. The alloy ingot is turned over and the melting is repeated 5 times. After cooling, the alloy ingot is crushed by a vibration mill for 20 s. After screening, a 300-mesh powder hydrogen storage alloy is obtained.
[0034] Comparative Example 6 A TiFe hydrogen storage alloy, the alloy composition is: Ti 52 Fe 47Co1Nb2La2, comprising Ti, Fe, Co, Nb and La in a stoichiometric ratio of 52:47:1:2:2, and a preparation method thereof comprising the following steps: According to Ti 52 Fe 47 The Co1Nb2La2 alloy components are prepared according to the stoichiometric ratio. The purity of the metal raw materials is greater than 99%, and the total mass of the alloy is 10 g. The raw materials are then melted in a vacuum arc with a melting current of 150A, a melting temperature of 2500-3000°C, an argon pressure of 600Pa, and each melting time of 3min. The alloy ingot is turned over and the melting is repeated 5 times. After cooling, the alloy ingot is crushed by a vibration mill for 20 s. After screening, a 300-mesh powder hydrogen storage alloy is obtained.
[0035] Comparative Example 7 A TiFe hydrogen storage alloy, the alloy composition is: Ti 52 Fe 46 Cr2Nb2La2, comprising Ti, Fe, Cr, Nb and La in a stoichiometric ratio of 52:46:2:2:2, and a preparation method thereof comprising the following steps: According to Ti 52 Fe 46 The stoichiometric ratio of the Cr2Nb2La2 alloy components is used for mixing. The purity of the metal raw materials is greater than 99%, and the total mass of the alloy is 10 g. The raw materials are then melted in a vacuum arc with a melting current of 150A, a melting temperature of 2500-3000°C, an argon pressure of 600Pa, and a melting time of 3min each time. The alloy ingot is turned over and the melting is repeated 5 times. After cooling, the alloy ingot is crushed by a vibration mill for 20 s. After screening, a 300-mesh powder hydrogen storage alloy is obtained.
[0036] Comparative Example 8 A TiFe hydrogen storage alloy, the alloy composition is: Ti 52 Fe 45 Cr2Co1Nb2La2, comprising Ti, Fe, Cr, Co, Nb and La in a stoichiometric ratio of 52:45:2:1:2:2, and a preparation method thereof comprising the following steps: According to Ti 52 Fe 45 The stoichiometric ratio of the Cr2Co1Nb2La2 alloy components is used for mixing. The purity of the metal element raw materials is greater than 99%, and the total mass of the alloy is 10 g. The raw materials are then melted in a vacuum arc with a melting current of 150A, a melting temperature of 2500-3000°C, an argon pressure of 600Pa, and a melting time of 1 min each time. The alloy ingot is turned over and the melting is repeated twice. After cooling, a block hydrogen storage alloy is obtained.
[0037] Comparative Example 9 A TiFe hydrogen storage alloy, the alloy composition is: Ti 52 Fe 45 Cr2Co1Nb2La2, comprising Ti, Fe, Cr, Co, Nb and La in a stoichiometric ratio of 52:45:2:1:2:2, and a preparation method thereof comprising the following steps: According to Ti 52 Fe 45 The stoichiometric ratio of the Cr2Co1Nb2La2 alloy components is used for formulation. The purity of the metal raw materials is greater than 99%, and the total mass of the alloy is 10 g. The raw materials are then melted in a vacuum arc with a melting current of 220A, a melting temperature exceeding 3000°C, an argon pressure of 600Pa, and a melting time of 3min each time. The alloy ingot is turned over and the melting is repeated 5 times. After cooling, the alloy ingot is crushed by a vibration mill for 20 s. After screening, a 300-mesh powder hydrogen storage alloy is obtained.
[0038] Performance testing 1. XRD data: The hydrogen storage alloys prepared in the embodiments and comparative examples were tested using an X-ray powder diffractometer (D8 Advance) produced by Bruker AXS GmbH of Germany. The test conditions were: Cu kα rays at an angle of 20-90°. The lattice parameters of the TiFe main phase were calculated from the XRD data. The test results are shown in Table 1 below.
[0039] 2. Hydrogen storage performance: The PCT equipment (MH-PCT) of China Youyan Technology Co., Ltd. was used to test the hydrogen storage performance of the alloys prepared in the examples and comparative examples. The time for the initial hydrogen absorption to reach the maximum hydrogen storage capacity at room temperature is the time taken for the sample to directly absorb hydrogen at a hydrogen pressure of 7 MPa without any heat treatment at room temperature until the maximum hydrogen storage capacity is reached; the reversible hydrogen absorption and desorption pressure-composition-isothermal characteristic curve (PCT) was tested at 40°C, the hydrogen pressure range was 0.001 MPa-9.5 MPa, the maximum hydrogen storage capacity was the maximum hydrogen storage capacity obtained by the PCT image, and the effective hydrogen storage capacity was the hydrogen storage capacity corresponding to the desorption to 0.1 MPa. The test results are shown in Tables 1 and Figure 2 shown.
[0040] 3. Cycle capacity retention rate: The hydrogen storage alloys prepared in the embodiments and comparative examples absorbed hydrogen at 3 MPa and 25°C for 25 min, and then dehydrogenated at 300°C for 15 min, which was recorded as one cycle. After 200 cycles, the alloys absorbed hydrogen at 40°C and 9.5 MPa hydrogen pressure. The ratio of the hydrogen storage capacity after 200 cycles to the maximum hydrogen storage capacity was the 200 cycle capacity retention rate. The test results are shown in Table 1 below.
[0041] Table 1 - Performance test results of hydrogen storage alloys prepared in the present application examples and comparative examples As shown in Table 1, compared with Example 1, Comparative Example 1 increases the proportion of Laves phase (AB2 structure) due to the increase in Cr content, improves the activation performance of the hydrogen storage alloy, but the hydrogen absorption and desorption platform is more inclined, resulting in a decrease in the maximum hydrogen storage capacity.
[0042] As shown in Table 1, compared with Example 1, in Comparative Example 2, due to the increase in Nb content, the lattice parameter of the TiFe main phase increases, thereby increasing the maximum hydrogen storage capacity, but the hydrogen absorption and desorption platform decreases, resulting in an increase in residual hydrogen and a decrease in effective hydrogen storage capacity.
[0043] As shown in Table 1, compared with Example 1, Comparative Example 3 has an increased Co content, which increases the flatness of the hydrogen absorption and desorption platform, but reduces the lattice parameters of the TiFe main phase, resulting in a decrease in the maximum hydrogen storage capacity and the effective hydrogen storage capacity, and the activation performance deteriorates, and the time for the initial hydrogen absorption to reach the maximum hydrogen storage capacity is prolonged.
[0044] As shown in Table 1 and Figure 2 As shown, compared with Example 1, Comparative Example 4 lacks the addition of Cr, Co and Nb, resulting in a decrease in the maximum hydrogen storage capacity and the effective hydrogen storage capacity, an increase in hysteresis, a deterioration in activation performance, and a prolongation of the time for the initial hydrogen absorption to reach the maximum hydrogen storage capacity.
[0045] As shown in Table 1, compared with Example 1, Comparative Example 5 lacks the addition of the rare earth element La, resulting in poor activation performance and cycle performance of the hydrogen storage alloy, reduced capacity retention after 200 cycles, and prolonged time for the initial hydrogen absorption to reach the maximum hydrogen storage capacity.
[0046] As shown in Table 1, compared with Example 1, Comparative Example 6 lacks the addition of Cr, resulting in poor activation performance of the hydrogen storage alloy, prolonged time for the initial hydrogen absorption to reach the maximum hydrogen storage capacity, decreased lattice parameters of the TiFe main phase, and reduced maximum hydrogen storage capacity and effective hydrogen storage capacity.
[0047] As shown in Table 1, compared with Example 1, Comparative Example 7 lacks the addition of Co, resulting in a more inclined hydrogen absorption and desorption platform, and a corresponding reduction in the effective hydrogen storage capacity.
[0048] As shown in Table 1, compared with Example 1, the hydrogen storage alloy of Comparative Example 8 was not subjected to vibration treatment, and it was difficult to directly absorb hydrogen in the block test, resulting in a significantly longer time for the initial hydrogen absorption to reach the maximum hydrogen storage capacity, and the smelting time and number of times were short, resulting in uneven internal elements of the hydrogen storage alloy, affecting the hydrogen storage capacity. As shown in Table 1, relative to Example 1, the smelting current of the hydrogen storage alloy of Comparative Example 9 was 220A, and the smelting temperature far exceeded 3000°C. Under this temperature condition, the Cr, Co and La elements in the alloy will partially volatilize, resulting in a reduction in the content of Cr, Co and La, a prolonged activation time of the synthesized hydrogen storage alloy, and a decrease in the cycle performance.
[0049] The specific embodiments described above further illustrate the purpose, technical solutions and beneficial effects of the present invention. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the scope of protection of the present invention. It is particularly pointed out that for those skilled in the art, any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention should be included in the scope of protection of the present invention.
Claims
1. A high-capacity and easily activated TiFe hydrogen storage alloy, characterized in that: The general formula of the hydrogen storage alloy is: Ti a Fe 49-b- c Cr b Co1N c RE d , among which, 50≤a≤55, 2≤b≤4, 1≤c≤5, 1≤d≤4, and RE is a rare earth element.
2. A high capacity and easily activated TiFe hydrogen storage alloy as claimed in claim 1, characterized in that: The RE is at least one of La, Ce, Y, Sm and Pr.
3. A high capacity and easily activated TiFe hydrogen storage alloy as claimed in claim 1, characterized in that: The hydrogen storage alloy is composed of Ti 52 Fe 45 Cr2Co1Nb2La2、Ti 50 Fe 43 Cr4Co1Nb2Y2、Ti 55 Fe 46 Cr2Co1Nb1Pr3、Ti 52 Fe 42 Cr2Co1Nb5Ce1、Ti 53 Fe 45 Cr3Co1Nb1La1、Ti 50 Fe 45 Any one of Cr2Co1Nb2La4.
4. A method for preparing a high-capacity and easily activated TiFe hydrogen storage alloy as claimed in any one of claims 1 to 3, characterized in that: The following steps are involved: The ingredients are prepared according to the stoichiometric ratio of the hydrogen storage alloy components, and then the raw materials are melted by arc melting. The melting time is 3-10 minutes each time, and the melting is repeated 5-10 times. The melting temperature does not exceed 3000° C. After cooling, the raw materials are crushed and sieved to obtain a powdered hydrogen storage alloy.
5. The method for preparing a high-capacity and easily activated TiFe hydrogen storage alloy according to claim 4, characterized in that: The raw material of the hydrogen storage alloy is a metal single substance with a purity of more than 99%.
6. The method for preparing a high-capacity and easily activated TiFe hydrogen storage alloy according to claim 4, characterized in that: During the smelting process, the smelting current is 120-180A and the inert gas pressure is 400-800Pa.
7. The method for preparing a high-capacity and easily activated TiFe hydrogen storage alloy according to claim 6, characterized in that: The inert gas is at least one of argon, nitrogen and helium.
8. The method for preparing a high-capacity and easily activated TiFe hydrogen storage alloy according to claim 4, characterized in that: The mesh size of the hydrogen storage alloy is 200-400 meshes.
9. The method for preparing a high-capacity and easily activated TiFe hydrogen storage alloy according to claim 4, characterized in that: The alloy ingot was crushed by a vibration mill, and the vibration milling time was 10-20 s.
10. The method for preparing a high-capacity and easily activated TiFe hydrogen storage alloy according to claim 4, characterized in that: The melting temperature is 2500-3000℃.
Citation Information
Patent Citations
Diphase hydrogen storage alloy
CN101704512A
Easy-to-activate hydrogen storage alloy and manufacturing method thereof and smelting equipment
CN110106426A
Rare earth compounded TiFe hydrogen storage alloy as well as preparation method and application thereof
CN118007000A
TiFe-based hydrogen storage alloy activated at room temperature as well as preparation method and application of TiFe-based hydrogen storage alloy
CN118726814A
Ferro-titanium base hydrogen storage alloy
CN1248637A